2014 IEEE Applied Power Electronics Conference and Exposition - APEC 2014 2014
DOI: 10.1109/apec.2014.6803394
|View full text |Cite
|
Sign up to set email alerts
|

Silicon-embedded toroidal inductors with magnetic cores: Design methodology and experimental validation

Abstract: An approach to the ultimate integration and miniaturization of MEMS-based 3-D magnetic components involves embedding the volume of the magnetic structures within the volume of the silicon wafer itself, exploiting microfabricated windings to create current paths, and utilizing embedded magnetic cores within the limited footprint of these components to boost the magnetic performance. However, this embedding approach imposes volumetric and microfabrication constraints that require an unusual magnetic component op… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…For integrated ferrite-based microinductors, some authors have sintered the bottom ferrite layer for spiral-type inductors then completed it with a composite top layer [8], some have sintered the bottom and top ferrite layer in-situ [25]. Others have developed hybrid solutions where the core is fabricated off-chip [15].…”
Section: Soft Ferrite Cores Characterization For Integrated Micro-ind...mentioning
confidence: 99%
See 1 more Smart Citation
“…For integrated ferrite-based microinductors, some authors have sintered the bottom ferrite layer for spiral-type inductors then completed it with a composite top layer [8], some have sintered the bottom and top ferrite layer in-situ [25]. Others have developed hybrid solutions where the core is fabricated off-chip [15].…”
Section: Soft Ferrite Cores Characterization For Integrated Micro-ind...mentioning
confidence: 99%
“…A lot of research has been carried out to achieve inductor integration on-chip or in-package. Some demonstrators of air-core inductors, such as thin film magnetic inductors and ferrite based ones, have shown that each integration method has its own merits and difficulties [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15]. For on-chip integration, approaches to the fabrication of micro-inductors involving vacuum deposition and electrodeposition of magnetic cores have been demonstrated over the last thirty years.…”
Section: Introductionmentioning
confidence: 99%